COMPARATIVE PERSPECTIVES ON ARBITRARY DEPRIVATION OF NATIONALITY AND REFUGEE STATUS. Issue 1 (15th December 2014) - Unknown
Abstract: The question of whether arbitrary deprivation of nationality constitutes persecution for the purposes of a determination of refugee status has received increased attention in recent jurisprudence. However, no systematic argument has been made to date on the ordinary meaning of words, context, object and purpose of Article 1A(2) of the 1951 Convention Relating to the Status of Refugees as it applies to stateless refugees. This is an important question because the absence of determination procedures and a protection regime specifically for stateless persons in many jurisdictions makes refugee and/or complementary protection the only options. This article examines existing landmark judicial decisions worldwide, relevant UN documents, and academic writing on whether arbitrary deprivation of nationality, either on its own or when taken with other forms of harm, amounts to persecution within the meaning of Article 1A(2) of the 1951 Refugee Convention, and if so on what grounds. It concludes by suggesting when (arbitrary) deprivation of nationality should lead to a finding of persecution, based on good practice, and points to a global consensus on a new rights perspective concerning nationality.